As expressões nominais referenciais na construção do humor nas crônicas de Agamenon - Magela, Maíra Mendes (2017)
This dissertation is inserted in the sociocognitive and interactional perspective in order to analyse the reference in the Agamemnon chronicles, published in the months of June and July of 2015, it seeks theoretical-methodological support in the works of Mondada and Dubois (2003 [1995]), Apothéloz (2003 [1995]), Conte (2003 [1996]), Francis (2003 [1994]), Cavalcante (2011), Koch (2004), Koch and Marcuschi (1998), Koch and Elias (2006, 2009) and Van Dijk (2012). The research aims to investigate how Luiz Inácio Lula da Silva and Dilma Rousseff speech objects are presented and retrieved for maintenance and textual progression, as well as to investigate, in the discursive dynamics, the participation of these referential processes to produce humor in the chronicles which compose the corpus of this thesis. Therefore, this work is based on the conceptions of humor from Possenti (1998), Travaglia (1990), Lins (2012, 2015), Bergson's (1987) and Propp (1982), from the semantic descriptions proposed by Raskin (1987) in the theory of Semantic Humor Script, as well as the endeavours works by Lins and Gonçalves (2012) and Tafarello (2014). In order to analyse and describe how the irony is established, it was based on Paiva’s (1961) work, regarding linguistic resources that attribute irony and comedy to the text. The proposal of this work is relevant for language study, since it seeks to find a relation between the referential processes and the humor establishment in the text, thus constituting an interdisciplinary study. The analysis reveals that referential nominal expressions attribute humor to the text, since the deflagration of humor can be related to linguistic mechanisms or ideological, historical, social, cognitive and cultural.